2014
DOI: 10.1128/aac.02667-14
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-Blind, Placebo-Controlled Clinical Trial of a Two-Day Regimen of Dihydroartemisinin-Piperaquine for Malaria Prevention Halted for Concern over Prolonged Corrected QT Interval

Abstract: f Dihydroartemisinin-piperaquine, the current first-line drug for uncomplicated malaria caused by Plasmodium falciparum and Plasmodium vivax in Cambodia, was previously shown to be of benefit as malaria chemoprophylaxis when administered as a monthly 3-day regimen. We sought to evaluate the protective efficacy of a compressed monthly 2-day treatment course in the Royal Cambodian Armed Forces. The safety and efficacy of a monthly 2-day dosing regimen of dihydroartemisinin-piperaquine were evaluated in a two-arm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 31 publications
3
52
1
Order By: Relevance
“…This finding supports the general recommendation for a 3-h fast before and after dosing. The slope estimate (0.05 ms per ng/ml, or an increase of 5 ms for every 100 ng/ml piperaquine) of the piperaquine exposure-QT interval response from the pooled analysis is similar to that described in recent publications (3,13). The QT-lengthening effects of piperaquine have been observed in clinical studies for more than a decade.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…This finding supports the general recommendation for a 3-h fast before and after dosing. The slope estimate (0.05 ms per ng/ml, or an increase of 5 ms for every 100 ng/ml piperaquine) of the piperaquine exposure-QT interval response from the pooled analysis is similar to that described in recent publications (3,13). The QT-lengthening effects of piperaquine have been observed in clinical studies for more than a decade.…”
Section: Discussionsupporting
confidence: 55%
“…In 2012, a follow-on randomized, double-blind, placebo-controlled study evaluating a 2-day DP regimen as a monthly malaria prevention therapy was halted after 4 out of 69 volunteers met prespecified criteria to stop the study because of individual cardiac safety endpoints with a QTcF prolongation of Ͼ500 ms. An unblind review by the Data Safety Monitoring Board (DSMB) revealed a 46-ms mean QTcF prolongation over that achieved with placebo at the time of the maximum plasma concentration (C max ) of piperaquine on day 2. A moderate, statistically significant correlation between the piperaquine concentration and the QTcF increase over the baseline was observed, and a strong correlation was observed for the four volunteers whose findings precipitated the cessation of the study (3). Lastly, in 2013 there was a moderate correlation between the piperaquine concentration and corrected QT interval (QTc) interval changes when DP was used as a 3-day regimen for the treatment of P. falciparum infection, though the effect was less pronounced than that found in the previous studies (5).…”
mentioning
confidence: 92%
See 3 more Smart Citations